A Symptomatic Reading on Meyer’s Twilight Series: Some Vicarious Lessons Overview - Imelda S. Lolowang (Universitas Batanghari Jambi, 2023)
This paper analyzes the problems or conflicts related to the character of Bella Swan who colors the plot in the Twilight series written by Stephenie Meyer, a popular literary romance genre with a vampire theme, a New York Times Best Seller, that consists of four (4) series, namely Twilight, New Moon, Eclipse, and Breaking Dawn. The author uses the Symptomatic Reading theory based on several expert opinions and basic theories about romance and fantasy, as well as several other expert opinions about this work. Written from the perspective of the main character, Bella, the four Twilight series explicitly and implicitly show some of the problems or conflicts that Bella experienced as a young girl approaching adulthood. The conflicts she experiences stem from his family, herself, and her love life. By analyzing this series of novels, the author not only presents the differences between ideological matters and the facts or reality of the main character's problems, but also raises a new understanding or perhaps more precisely an acknowledgment of the realities that underlie family circumstances, choices and desires of an individual like Bella. Through this analysis, some values or discussions can be drawn and overviewed and can be taken into consideration for the teaching and learning in literature classes, or for the general readers and movie goers in general; bearing in mind that popular literature is no longer a topic to be taken lightly, but must be criticized and benefited from in this era of media and technology, which, in turn, greatly influences the popular culture itself. Thus, it is hoped as well that there will be a balance in knowledge and decision-making in discussions about popular literature.